Voltammetry at a Hanging Mercury Drop Electrode as a Tool for the Study of the Interaction of Double-stranded DNA with Genotoxic 4-Nitrobiphenyl; Electroanalysis; Vol. 28, iss. 11 - Horakova E. Eva (2016, 2016)
Title screen